Rethinking the bronze-iron transition in Iran: copper and iron metallurgy before the Achaemenid Period - Cuénod, A; A.M.A. Cuenod (2012)
Iran, a country rich in mineral resources, has a long history of metal working. Copper objects first appeared in the 7th millennium BC and in the following millennia, copper became the material of choice for the production of many objects. Artefacts of iron began to appear in the mid 2nd millennium BC and by the mid 1st, iron had replaced bronze for most uses, but the reasons for this change remain unclear. This thesis seeks to examine the transition from bronze to iron metallurgy from a new angle. By looking at changes in copper-based metallurgy between the Bronze Age and the Iron Age, it attempts to better understand the context in which iron metallurgy developed. To that end, the results of previously published chemical analyses of over 5000 copper-based objects from Iran and neighbouring regions and the lead isotope analyses of about 380 objects were assembled in a database. The tin, arsenic, nickel, antimony and silver concentrations in particular are studied. The data is divided into 16 metal groups based on the absence or presence of the latter four elements. The study of the main groups allows us to describe interesting new patterns of metal movement and recycling. It appears that before the end of the Bronze Age, a number of copper sources and/or trade routes from both east and west declined, leading to a reliance on more local sources for copper and tin in the Iron Age. The practice of recycling from the 3rd millennium BC onward is also evidenced. Overall, it seems that iron appeared within a thriving bronze industry, with a good access to metal resources and a developed understanding of the possibilities offered by copper (alloying, recycling, mixing…). Was it then the more ‘permanent’ nature of iron that attracted the ancient metal-workers and led to its advent?